Examining the Contribution of Valuable and Rare Resources and Capabilities to Performance of Micro Enterprises - Moscare-Balanquit, Daisy Lily (International Review of Management and Marketing, 2021)
This article examined the contribution of resources and capabilities to the competitiveness and performance of micro enterprises within the context of resource-based view. Cross-sectional survey design was employed. The data came from 183 registered micro enterprises in Catarman. The result showed that the value of resource-capability combinations is inversely related to competitive advantage, while the rareness of resource-capability combinations is positively related. The direct and indirect effects of competitive advantage between value and rareness of resource-capability combinations and performance were established. The moderating effect of business age between competitive advantage and performance was determined. This study added support to the application of resource-based view to micro enterprises in rural areas in a developing economy and unravel important implications for micro enterprises in Catarman. Keywords: micro enterprise; resources; capabilities; competitive advantage; performance JEL Classifications: M1, M2 DOI: https://doi.org/10.32479/irmm.11285